The Female Vote and the Rise of AKP in Turkey - Jan Fidrmuc; Cigdem Börke Tunali (Center for Economic Studies and ifo Institute (CESifo), 2015)
Differences between the voting behavior of men and women have become one of the most significant issues in social science research in recent years. In this study, we examine whether there is gender gap in voting behavior in Turkey. Using European Social Survey data, we find that education level and religiosity are the main determinants of voting behavior of both men and women in Turkey. There are significant differences between the genders, nevertheless. In particular, the effect of education on the support for the Justice and Development Party (AKP) and the Republican People's Party (CHP) among male and female voters was different in the general election held in 2002. We argue that this outcome may be driven by the different labor-market implications of Islamization for male and female workers with intermediate skills.
Keywords: O15; P48; Z12; 330; gender gap; voting; Turkey; Justice and Development Party (AKP); Republican People's Party (CHP); democracy; Islam